Association Between End-Tidal Carbon Dioxide Pressure and Cardiac Output During Fluid Expansion in Operative Patients Depend on the Change of Oxygen Extraction. Issue 14 (April 2016) - Guinot, Pierre-Grégoire; Guilbart, Mathieu; Hchikat, Abdel Hakim; Trujillo, Marie; Huette, Pierre; Bar, Stéphane; Kirat, Kahina; Bernard, Eugénie; Dupont, Hervé; Lorne, Emmanuel
Abstract : Abstract: In a model of hemorrhagic shock, end-tidal carbon dioxide tension (EtCO2 ) has been shown to reflect the dependence of oxygen delivery (DO2 ) and oxygen consumption (VO2 ) at the onset of shock. The objectives of the present study were to determine whether variations in EtCO2 during volume expansion (VE) are correlated with changes in oxygen extraction (O2 ER) and whether EtCO2 has predictive value in this respect. All patients undergoing cardiac surgery admitted to intensive care unit in whom the physician decided to perform VE were included. EtCO2, cardiac output (CO), blood gas levels, and mean arterial pressure (MAP) were measured before and after VE with 500 mL of lactated Ringer solution. DO2, VO2, and O2 ER were calculated from the central arterial and venous blood gas parameters. EtCO2 responders were defined as patients with more than a 4% increase in EtCO2 after VE. A receiver-operating characteristic curve was established for EtCO2, with a view to predicting a variation of more than 10% in O2 ER. Twenty-two (43%) of the 51 included patients were EtCO2 responders. In EtCO2 nonresponders, VE increased MAP and CO. In EtCO2 responders, VE increased MAP, CO, EtCO2, and decreased O2 ER. Changes in EtCO2 were correlated with changes in CO and O2 ER during VE ( P  < 0.05). The variation of EtCO2 during VE predicted a decrease of over 10% in O2 ER (area under the curve [95% confidence interval]: 0.88 [0.77–0.96]; P  < 0.0001). During VE, an increase in EtCO2 did not systematically reflect an increase in CO. Only patients with a high O2 ER (i.e., low ScvO2 values) display an increase in EtCO2 . EtCO2 changes during fluid challenge predict changes in O2 ER.